HUKUM ADMINISTRASI NEGARA, AKUNTABILITAS, DAN PENCEGAHAN PENYALAHGUNAAN WEWENANG DALAM PENYELENGGARAAN PELAYANAN PUBLIK - Gunawan Widjaja (ADMIN: Jurnal Administrasi Negara, 2026)
Public service is a reflection of the effectiveness of administrative law in realising transparent and accountable good governance. This article analyses the role of HAN as a normative foundation that regulates the authority of public officials, ensures vertical and horizontal accountability, and prevents the abuse of authority through regulations such as Law No. 30 of 2014 on Government Administration and Law No. 25 of 2009 on Public Service. Using a normative legal literature review approach, this study identifies that accountability within HAN encompasses not only formal accountability through the Government Agency Performance Report (LKjIP) and the Government Agency Performance Accountability System (SAKIP), but also ethical dimensions and public participation, reinforced by oversight from the Indonesian Ombudsman, the Corruption Eradication Commission (KPK), and the digitalisation of the Public Service Delivery System (SPBE). Preventing the abuse of authority requires a multi-layered strategy encompassing Minimum Service Standards (SPM), integrity training for civil servants, a responsive administrative court system, and public social control through public information transparency. Key findings confirm that the synergy of law, technology, and organisational culture is the key to bureaucratic transformation towards clean, fair, and people-centred public service, as mandated by the constitution.